Electronic Governance that depends on Technology (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Many dimensions and factors influence the definition of e-governance. The word “electronic” in the term electronic governance means that governance that depends on technology. E-governance is the use of Information and Communication Technology (ICT) to deliver government services, exchange information of telecom transactions, and the integration of various stand-alone systems and services between government and citizen (G2C), between government and business (G2B) and between governments and each other (1).                     (G2G) as well as departmental operations and interactions within the whole-of-government framework. Through e-governance, government services available to citizens are provided in a convenient, efficient and transparent manner. The three main target groups that can be distinguished in the concepts of governance are government, citizens and corporations/interest groups. There are no clear boundaries in governance .